2018
DOI: 10.1002/jlcr.3651
|View full text |Cite
|
Sign up to set email alerts
|

177Lu‐DOTMP induces G2/M cell cycle arrest and apoptosis in MG63 cell line

Abstract: Bone pain is the major manifestation of skeletal metastases. Although various treatment modalities are available for bone pain palliation, use of radiolabeled phosphonates is documented to be more effective. Among radionuclides available for this purpose, lutetium-177 is gaining popularity due to its moderate beta energy, theranostic capability, favorable half-life and convenient production logistics. Lu-DOTMP has shown considerable promise as a metastatic bone pain palliating agent in preliminary evaluations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Kumar et al . in cell culture studies found that 177 Lu-DOTMP induces apoptotic death of malignant cells by cell cycle arrest at the G2/M phase and might be one of the causes for palliative effect [12]. The patients treated with 177 Lu-DOTMP in the present study achieved an overall response rate of 77%, similar to that of 89 SrCl 2 [11].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Kumar et al . in cell culture studies found that 177 Lu-DOTMP induces apoptotic death of malignant cells by cell cycle arrest at the G2/M phase and might be one of the causes for palliative effect [12]. The patients treated with 177 Lu-DOTMP in the present study achieved an overall response rate of 77%, similar to that of 89 SrCl 2 [11].…”
Section: Discussionmentioning
confidence: 63%
“…The follow-up bone scans may show a decrease in tumor size with reduction of osteoblastic lesions, suggesting a possible tumoricidal effect and thereby reducing the mechanical effect on the periosteal pain receptors [8,11]. Kumar et al in cell culture studies found that 177 Lu-DOTMP induces apoptotic death of malignant cells by cell cycle arrest at the G2/M phase and might be one of the causes for palliative effect [12]. The patients treated with 177 Lu-DOTMP in the present study achieved an overall response rate of 77%, similar to that of 89 SrCl 2 [11].…”
Section: /188mentioning
confidence: 99%
“…45 Kumar et al also demonstrated a dose-dependent apoptosis induction and G2/M arrest with 177 Lu-DOTMP in human osteosarcoma (MG-63) cell lines indicating the apoptosis inducing tendency of 177 Lu. 58 Analysis of the apoptotic data further confirmed that induction of overall cytotoxicity by radiation is inversely proportional to HER2 overexpression. The findings of this study are akin to the observations by other authors that overexpression of HER2 suppresses apoptosis owing to mechanisms that disrupt both the intrinsic and extrinsic apoptotic pathways.…”
Section: Discussionmentioning
confidence: 82%
“…Notably, studies have demonstrated that 177 Lu induces apoptotic cell death by activating the apoptotic signaling pathway through the downregulation of anti-apoptotic B-cell lymphoma 2 (bcl-2) family genes in human histiocytic lymphoma [139]. In osteosarcoma cell lines, 177 Lu conjugated to ethylenediamine tetramethylene phosphonic (EDTMP) and 1,4,7,10-tetraazacyclododecane-1,4,7,10tetramethylene phosphonic acid (DOTMP) induces G2/M phase cell cycle arrest [143] and DNA fragmentation-associated apoptotic cell death. This is achieved by downregulating bcl-2 and cleavage of the PARP protein, which serves as a substrate for active caspase-3 during cell death [144].…”
Section: Radioisotopes Emitting Low-let Particles Beta Particle Emittersmentioning
confidence: 99%